Analysis of the Recitation Method in Improving Islamic Religious Education Learning Outcomes of Elementary School - Dandi; Anirah, Andi; Erniati (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2026)
Islamic Religious Education (IRE) plays a vital role in fostering students’ religious knowledge, attitudes, and practical skills. Effective learning at the elementary school level requires instructional approaches that promote active participation and responsibility. One such approach is the recitation method, which involves task assignment, task completion, and accountability for learning outcomes. This study aimed to examine the implementation of the recitation method in Islamic Religious Education and to explore teachers’ and students’ perceptions of its impact on learning. A qualitative descriptive approach was employed at SDN 3 Bajugan, Tolitoli Regency. The participants included the school principal, an Islamic Religious Education teacher, and fifth-grade students. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using the interactive model of Miles and Huberman, comprising data reduction, data display, and conclusion drawing. The findings revealed that the recitation method was implemented through three stages: task assignment, task completion, and task accountability. Both teachers and students perceived the method as enhancing classroom participation, learning responsibility, and engagement. Students also demonstrated improved understanding of the learning materials and greater confidence in performing religious practices. The study concludes that the recitation method has become an integral component of Islamic Religious Education instruction and is perceived as an effective strategy for promoting active learning and strengthening students’ responsibility. Abstrak: Pendidikan Agama Islam (PAI) berperan penting dalam mengembangkan pengetahuan, sikap, dan keterampilan keagamaan peserta didik. Pembelajaran di sekolah dasar memerlukan pendekatan yang mendorong partisipasi aktif dan tanggung jawab peserta didik. Salah satu metode yang digunakan adalah metode resitasi, yang mencakup pemberian tugas, pelaksanaan tugas, dan pertanggungjawaban hasil tugas. Penelitian ini bertujuan mendeskripsikan implementasi metode resitasi dalam pembelajaran Pendidikan Agama Islam serta persepsi guru dan peserta didik terhadap hasil belajar selama penerapannya. Penelitian menggunakan pendekatan deskriptif kualitatif di SDN 3 Bajugan, Kabupaten Tolitoli. Partisipan terdiri atas kepala sekolah, guru Pendidikan Agama Islam, dan peserta didik kelas V. Data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa metode resitasi diterapkan melalui tiga tahap, yaitu pemberian tugas, pelaksanaan tugas, dan pertanggungjawaban tugas. Guru dan peserta didik memandang metode ini mampu meningkatkan partisipasi belajar, tanggung jawab dalam menyelesaikan tugas, serta keterlibatan selama pembelajaran. Peserta didik juga menunjukkan pemahaman materi yang lebih baik dan kepercayaan diri yang lebih tinggi dalam praktik keagamaan. Penelitian ini menyimpulkan bahwa metode resitasi menjadi bagian penting dalam pembelajaran Pendidikan Agama Islam dan dipersepsikan efektif dalam mendukung pembelajaran aktif serta penguatan tanggung jawab peserta didik.